AKTIVITAS BOM IKAN DAN PRODUKSI MINUMAN KERAS TRADISIONAL DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN DAN PENDEKATAN PARIWISATA BERBASIS MASYARAKAT - Singgalen, Yerik Afrianto (Universitas Kristen Satya Wacana, 2016)
This Study aims to identify the potential of tourism as well as the various activities that have a negative impact on the environment, economic and social in Tunuo village. Furthermore, this study communicate these issues in a sustainable development perspective and community based tourism approach. This study used a qualitative method with case study approach. Observation, in-depth interviews are used to obtain the data. Triangulation technique is also used to obtain valid information. This study was conducted in North Halmahera since the end of 2014. The Finding of this study is a push and pull factors such as education, employment, needs, revenue, market demand and resources availability. Through this research, tourism development can be a strategy to suppress all the problem that has a negative impact on the environment, social and economic in Tunuo Village.